ANALYSIS OF THE EFFECT OF TRANSCRANIAL MAGNETIC STIMULATION ON PERIPHERAL BLOOD CIRCULATION AND REDOX PROCESSES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND POLYNEUROPATHY - Шумейко, Надежда Ивановна; Ямщикова, Анастасия Валерьевна; Филимонов, Сергей Николаевич; Маклакова, Татьяна Петровна; Каширина, Евгения Петровна (Medicine in Kuzbass, 2025)
The methods of the effect of transcranial magnetic stimulation in type 2 diabetes mellitus patients with progressive damage to the microcirculatory bed and distal neuropathy were analyzed, new diagnostic and therapeutic methods were searched for to improve peripheral blood circulation and redox processes in these patients. The expediency of using the Laser Doppler fluometry (LDF) method in patients with type 2 diabetes mellitus (DM) with distal neuropathy during transcranial magnetic stimulation (TMS) therapy has been determined. LDF is a relatively new non-invasive method for studying microcirculation, which allows to assess the overall level of peripheral perfusion and features of blood flow regulation in the microcirculatory bed in 20 patients with DM of both genders aged 44 to 75 years old suffering from DM for 5 to 14 years, with HbA1c levels of 7.6-11.8%. These patients underwent LDF and fluorescence diagnostics using LAKK-M device before and after short-term TMS sessions for 3 days. LDF was performed on the palm surface of the left ring finger according to generally accepted methods. Statistically significant changes in microcirculation (PM), vascular tone (CT), intravascular resistance (Rc) and cardiac spectra were obtained. According to the fluorescence diagnosis, the indicators of oxidative metabolism of porphyrins and NADH reacted most clearly to TCMS. It turned out that in 13 patients, CT and porphyrin levels were predominantly reduced, whereas in 7 subjects, a decrease in Rc and changes in NADH prevailed, and the most pronounced decrease in cardiac spectra was found. There were no correlations between the studied parameters and indicators of carbohydrate and lipid metabolism, duration of diabetes, gender and age. Clinically, positive dynamics were revealed in the form of a decreased leg pain, improved sleep and performance, draws attention to the sudden appearance of drowsiness immediately after TMS and a decrease in blood sugar. Short-term TMS is accompanied by an increase in the volumetric characteristics of microhemodynamics and possibly a potential improvement in the transport function of blood and transcapillary metabolism and tissue trophism. These TMS effects in patients with type 2 diabetes mellitus and polyneuropathy make it possible to determine the method of LDF and fluorescence, which reveals disorders of the microcirculatory bed and tissue metabolism and requires further study and implementation into clinical practice.